Prevalence of Congenital Hypothyroidism in Neonates - Bushra Batool, Sehar Saba Samuel, Javeria Shamim, Mohammad Mohsin Khan, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To determine the frequency of congenital hypothyroidism in neonates. Patients and Methods: A total number of 200 neonates born through SVD and cesarean section after 37 weeks of gestation aged 48 hours of birth to 2 weeks of neonatal age (as serum of neonates less than 48 hours of life contain mother’s serum level of TSH were included. The study was conducted from 05-Nov-2020 to 04-May-2021. Data regarding neonates’ age, gender, weight, and height was taken. 2cc venous blood was taken for serum TSH and T4 level. Neonates having TSH hormone level more than 20mIU/mL were labelled as having congenital hypothyroidism (CH). Results: Mean age of neonates was 9.63±3.94 days. There were 113 (56.50%) females and 87 (43.50%) male neonates. Mean weight of neonates was 2970.28±516.32 grams. Mean height of neonates was 52.23±2.11 cm. Mean gestational age was weeks. Mean occipitofrontal circumference of neonates was 34.69±1.29 cm. Mean TSH level were 6.64±7.92 mIU/L. Mean T4 level was 23.70±4.25 µg/dL. CH was diagnosed in 4 (2.0%) neonates. Conclusion: Congenital hypothyroidism (CH) is common among neonates. In present study CH was diagnosed in 2.0% neonates who were screened for CH. So CH screening should be done in all neonates to diagnose CH at early stages and to prevent complication of CH in these neonates.